Insulin-Like Growth Factor -1 (IGF-1) and Glucose Dysregulation in Young Adult Patients with β-Thalassemia Major: Causality or Potential Link? : IGF-1 and glucose dysregulation in thalassemia - De Sanctis, Vincenzo; Soliman, Ashraf; Daar, Shahina; Tzoulis, Ploutarchos; Yassin, Mohamed A.; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2022)
Background: Insulin-like growth factor-1 (IGF-1) has been shown to lower blood glucose through stimulating glucose transport to fat and muscle and inhibiting hepatic glucose output. Although previous cross-sectional reports reported an association between low circulating concentrations of IGF-1 and glucose dysregulation (GD), its role is still debated. Aims of study: The present retrospective study was designed to assess the circulating IGF-1 levels in β-thalassemia major (β -TM) patients with normal oral glucose tolerance test (NGT-OGTT) and (GD) referred for an endocrine evaluation to explore the potential link between low IGF-1 and GD. Study design and methods: Our study included 34 young adult patients with β-TM; 12 patients with NGT after OGTT, 7 with impaired glucose tolerance (IGT), 9 with impaired fasting glucose (IFG) plus IGT, and 6 patients with β-TM-related diabetes mellitus (β-TM- DM). Results: Twenty-two β-TM patients with GD or β-TM- DM and 1 patient with NGT had IGF-1 levels below the 2.5th percentile. Correlation of IGF-1 with fasting plasma glucose, HOMA-IR (homeostatic model assessment for insulin resistance) and OGIS (oral glucose insulin sensitivity) was found. Moreover, a negative correlation was documented between ALT and the Insulinogenic Index (IGI) and a positive correlation between serum ferritin and PG 2-h after OGTT. Conclusion: This study reports for the first time an association between low levels of IGF-1 and GD in β-TM patients. Despite some limitations, our study can serve to generate proposals for more convenient and efficient methods to identify and treat early GD in patients with β-TM, and to conduct more extensive studies. www.actabiomedica.it)